Changes in surface glycosylation and glycocalyx shedding in Trichobilharzia regenti (Schistosomatidae) during the transformation of cercaria to schistosomulum. - Jana Řimnáčová; Libor Mikeš; Libuše Turjanicová; Jana Bulantová; Petr Horák (PLoS ONE, 2017)
The invasive larvae (cercariae) of schistosomes penetrate the skin of their definitive hosts. During the invasion, they undergo dramatic ultrastructural and physiological transitions. These changes result in the development of the subsequent stage, schistosomulum, which migrates through host tissues in close contact with host's immune system. One of the striking changes in the transforming cercariae is the shedding of their thick tegumental glycocalyx, which represents an immunoattractive structure; therefore its removal helps cercariae to avoid immune attack. A set of commercial fluorescently labeled lectin probes, their saccharide inhibitors and monoclonal antibodies against the trisaccharide Lewis-X antigen (LeX, CD15) were used to characterize changes in the surface saccharide composition of the neuropathogenic avian schistosome Trichobilharzia regenti during the transformation of cercariae to schistosomula, both in vitro and in vivo. The effect of various lectins on glycocalyx shedding was evaluated microscopically. The involvement of peptidases and their inhibitors on the shedding of glycocalyx was investigated using T. regenti recombinant cathepsin B2 and a set of peptidase inhibitors. The surface glycocalyx of T. regenti cercariae was rich in fucose and mannose/glucose residues. After the transformation of cercariae in vitro or in vivo within their specific duck host, reduction and vanishing of these epitopes was observed, and galactose/N-acetylgalactosamine emerged. The presence of LeX was not observed on the cercariae, but the antigen was gradually expressed from the anterior part of the body in the developing schistosomula. Some lectins which bind to the cercarial surface also induced secretion from the acetabular penetration glands. Seven lectins induced the shedding of glycocalyx by cercariae, among which five bound strongly to cercarial surface; the effect could be blocked by saccharide inhibitors. Mannose-binding protein, part of the lectin pathway of the complement system, also bound to cercariae and schistosomula, but had little effect on glycocalyx shedding. Our study did not confirm the involvement of proteolysis in glycocalyx shedding.